Blood Plasma Minerals and Biochemical Profile of Anestrus and Endometritic Cows Reared in Tribal Areas of Himachal Pradesh, India - Sharma, Ankita; Singh, Madhumeet; Kumar, Pravesh (The Indian Journal of Animal Reproduction, 2022)
Blood samples were collected from 227 infertile (Endometritis; n=123, Anoestrus; n=104) cows from five different tribal locations of Himachal Pradesh viz. Lahaul, Spiti, Kinnaur, Pangi and Bharmour. Significantly, lower levels of potassium were recorded in the Kinnaur district in both anestrus (3.33±0.09mmol/L) and endometritic (3.30±0.12mmol/L) cows as compared to other tribal areas. Significantly, higher levels of AST (p<0.01) were found in anestrus cows of Pangi (103.76±6.07 U/L) followed by Bharmour (93.34±14.43 U/L). The levels of cholesterol were significantly higher in anestrus cows of Lahaul (189.63±16.99 mg/dl) followed by Bharmour (184.54±19.57 mg/dl) and Pangi (162.03±13.83 mg/dl). The levels of creatinine were significantly higher (p<0.05) in anestrus cows of Spiti as compared to other tribal areas. The levels of ALT were significantly higher in anestrus cows of Spiti (37.22±2.01 U/L) followed by Pangi (34.44±3.19 U/L) and Lahaul (29.46±7.35 U/L). In the case of endometritic cows, values of ALT were significantly higher in Spiti (42.41±2.64 U/L) followed by Lahaul (23.37±4.9 U/L). The levels of total protein were found significantly higher in endometritic (8.34±0.31g/dl) cows of Lahaul as compared to other tribal areas.